Fall Detection on Ambient Assisted Living using a Wireless Sensor Network - Pereira, António; Felisberto, Filipe; Maduro, Luis; Felgueiras, Miguel (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2013)
In this work, a distributed system for fall detection is presented. The proposed system was designed to monitor activities of the daily living of elderly people and to inform the caregivers when a falls event occurs. This system uses a scalable wireless sensor networks to collect the data and transmit it to a control center. Also, an intelligent algorithm is used to process the data collected by the sensor networks and calculate if an event is, or not, a fall. A statistical method is used to improve this algorithm and to reduce false positives. The system presented has the capability to learn with past events and to adapt is behavior with new information collected from the monitored elders. The results obtained show that the system has an accuracy above 98%.